THE ROLE OF CLINICAL STAGES IN MAKING EFFICIENT THE THERAPEUTIC MANAGEMENT IN PARTIAL EDENTATION - Boariu Diana; Doriana Agop Forna; Iordache Cristina (Romanian Society of Oral Rehabilitation, 2018)
The aim of our study is to hierarchize the importance of the role of the main clinical stages of treatment in order to achieve a successful therapeutic management.Material and method:This study is carried out by analyzing the classic and modern facets for the main clinical stages that decisively influence the therapeutic development of an edented clinical case with different degrees of damage to the muco-bone, dento-periodontal support, with a special attention always being given loco-regional impairments. Results and disscusions :A particularly important aspect is represented by the management of devital teeth, which often, through the present and associated biomechanics, biomechanical stability orientates the choice of the restorative prosthetic solution to the zirconium ceramic restoration register, its opaque character being known, or to metalic-ceramice crowns. Conclusions:In view of efficient management of edentuous therapy, an effective clinical and paraclinical assessment is required, following the balancing, according to the decisional therapeutical algorithm of each clinical stage, and the manner in which it is performed in a classical or modern registry.